Unilateral Toxic Anterior Segment Syndrome Resulting in Cataract and Urrets-Zavalia Syndrome after Sequential Uneventful Implantation of a Posterior Chamber Phakic Toric Intraocular Lens at Two Different Surgical Facilities: A Series of Unfortunate Events - Kepa Balparda; Claudia Marcela Vanegas-Ramirez; Johny Márquez-Tróchez; Tatiana Herrera-Chalarca (Case Reports in Ophthalmological Medicine)
Background. Phakic Intraocular Lens (P-IOL) implantation is a safe, easy, predictable intervention designed to manage moderate to high refractive errors. Complications are relatively uncommon and include mainly cataract and intraocular pressure spikes. Toxic Anterior Segment Syndrome (TASS) is a rather unusual sterile anterior segment inflammation after uneventful intraocular surgery, extremely rarely reported after P-IOL implantation. Urrets-Zavalia Syndrome (UZS) is also very rarely described after P-IOL. To date, to the best of the authors’ knowledge, no article has ever described the simultaneous occurrence of TASS and UZS in a patient after P-IOL implantation. Objective. In this article, the authors present the case of a female patient with moderate myopic astigmatism, who underwent sequential P-IOL implantation at two different facilities. The postoperative course of the first eye was uneventful, but she developed complications associated to the intervention in the second eye. Materials. The article describes the case of a young patient who underwent a sequential Phakic Intraocular Lens (P-IOL) implantation at two different institutions. The postoperative course of the first eye (left eye) was uneventful; however, the second eye (right eye) initially developed Toxic Anterior Segment Syndrome (TASS). Although timely and correct management was instituted, upon resolution of TASS, the patient developed Urrets-Zavalia Syndrome, anterior subcapsular cataract, and significant endothelial damage in the same eye. Results. The patient was followed closely and managed accordingly; corneal edema and anterior segment inflammation of the right eye eventually resolved. Nevertheless, an anterior subcapsular cataract and a fixed dilated pupil remained; with normal intraocular pressure (IOP). Specular microscopy confirmed an endothelial cell loss in the TASS eye (right eye). Pupil size showed no reaction to repeated doses of Pilocarpine 2%. A month after surgery, refraction on her right eye was +0.25+0.75×93, which resulted in a 20/50 vision. Conclusions. TASS and UZS are both extremely rare complications after uneventful P-IOL implantation, with only a handful of cases having been reported of each of them. To date, this is the very first case where UZS ensued after and potentially as a consequence of TASS in a patient who had undergone P-IOL implantation. Although a direct causative element could not be pinpointed, the fact that the complication ensued after being operated in one surgical institution and not the other, could suggest some role of different sterilization and handling procedures, but no direct conclusion can be made on this case.